Species specificity profiling of rat and human organic cation/carnitine transporter Slc22a5/SLC22A5 (Octn2/OCTN2). Issue 3 (June 2017) - Szabó, Kitti; Nagy, Zoltán; Juhász, Viktória; Zolnerciks, Joseph K.; Csorba, Attila; Tímár, Zoltán; Molnár, Éva; Pádár, Petra; Johnson, William; Beéry, Erzsébet; Krajcsi, Péter
Abstract: The purpose of this study was to characterize the uptake of carnitine, the physiological substrate, and the uptake of 3-(2, 2, 2-trimethylhydrazinium)propionate, a consensus substrate by rat Octn2 and human OCTN2 transporters as well as to characterize drug-mediated inhibition ofl -carnitine uptake by the rat and human orthologs overexpressed in CHO-K1 cells.l -carnitine and 3-(2, 2, 2-trimethylhydrazinium)propionate were found to be a lower affinity substrate for rat Octn2 (KM = 32.66 ± 5.11 μM and 23.62 ± 4.99 μM respectively) than for human OCTN2 (KM = 3.08 ± 0.74 μM and 7.98 ± 0.63 μM). The intrinsic clearance (CLint ) value for carnitine was higher for the human than for the rat transporter (22.82 ± 5.57 ml/min*mg vs 4.008 ± 0.675 ml/min*mg). For 3-(2, 2, 2-trimethylhydrazinium)propionate, in contrast, the CLint value for rat Octn2 was higher than for human OCTN2 (323.9 ± 72.8 ml/min*mg vs 65.11 ± 5.33 ml/min*mg). Furthermore, many pharmacologically important drugs were shown to affectl -carnitine transport by Octn2/OCTN2. The correlation between the IC50 datasets for the rat and human transporter resulted in an r value of 0.47 (p > 0.05). However, the greatest difference was less than seven-fold and 13 of 15 compounds yielded a difference less than 3-fold. Thus, the transporters from these two species showed an overlapping but somewhat different substrate and inhibitor specificity.